ANALISA RCM PADA MOTOR DIESEL PENGGERAK GENERATOR DAYA 320 kVA SUMBER KELISTRIKAN DI HOTEL SAPADIA ROKAN HULU - Legisnal Hakim (Universitas Pasir Pengaraian, 2014)
When the supply of electricity in a hotel is off or at a local electricity grid is not able to distribute to thehotel, the hotel shall provide its own power supply using a generator driven by a Diesel Engine. Motor dieselis the motor that is also called Compression Ignition (